2015
DOI: 10.3892/etm.2015.2939
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 promotes keratinocyte proliferation via the downregulation of C/EBPα

Abstract: Abstract. Psoriasis vulgaris is a common chronic inflammatory skin disease characterized by the hyperproliferation and abnormal differentiation of keratinocytes. CCATT/enhancer binding protein α (C/EBPα) is abundant in the epidermis and is associated with the proliferation of keratinocytes. However, the role of C/EBPα in the proliferation of keratinocytes and the pathogenesis of psoriasis vulgaris are yet to be elucidated. In the present study, using two-step immunohistochemistry, the expression levels of C/EB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 28 publications
1
18
0
1
Order By: Relevance
“…The infiltrating dermal dendritic cells produce large amounts of TNF‐α and IL‐23 and induce the differentiation of IL‐17A–producing helper T (Th17) cells (Figure ) . IL‐17A upregulates the proliferation of keratinocytes and downregulates the differentiation of these cells . IL‐17A also upregulates the production of the neutrophil‐attracting cyto‐/chemokines IL‐36, CXCL1, CXCL2 and CXCL8 by keratinocytes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The infiltrating dermal dendritic cells produce large amounts of TNF‐α and IL‐23 and induce the differentiation of IL‐17A–producing helper T (Th17) cells (Figure ) . IL‐17A upregulates the proliferation of keratinocytes and downregulates the differentiation of these cells . IL‐17A also upregulates the production of the neutrophil‐attracting cyto‐/chemokines IL‐36, CXCL1, CXCL2 and CXCL8 by keratinocytes .…”
Section: Introductionmentioning
confidence: 99%
“…24,25 IL-17A upregulates the proliferation of keratinocytes and downregulates the differentiation of these cells. 26,27 IL-17A also upregulates the production of the neutrophil-attracting cyto-/chemokines IL-36, CXCL1, CXCL2 and CXCL8 by keratinocytes. 28,29 Moreover, IL-17A promotes keratinocytes to produce CCL20, which is an essential chemoattractant for CCR6 + Th17 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Down‐regulating Cebpa by CUGBP1 was reported to promote cell proliferation and suppress apoptosis in human non‐small cell lung cancers . Downregulation of Cebpa by IL‐17 promotes keratinocyte proliferation . It was also reported that the transcription factor Cebpa is a strong inhibitor of cell proliferation through cyclin‐dependent protein kinase 2 (cdk2) and cdk4 .…”
Section: Discussionmentioning
confidence: 99%
“…25 Downregulation of Cebpa by IL-17 promotes keratinocyte proliferation. 26 It was also reported that the transcription factor Cebpa is a strong inhibitor of cell proliferation through cyclin-dependent protein kinase 2 (cdk2) and cdk4. 27 Overexpression of Cebpa significantly decreased cell proliferation and upregulated the expression levels of the apoptosis-related genes Foxo3 and Bim in K562 cells.…”
Section: F I G U R E 3 Mir-486 Inhibits Expression Of Cebpa a Exprementioning
confidence: 99%
“…The concentration of IL-17A in the blood serum of healthy volunteers usually does not exceed 10 pg/mL (Shilova et al, 2015). In contrast, the biological effects of IL-17A in cultured epidermal keratinocytes and fibroblasts, such as activation of protein kinases (Peric et al, 2008(Peric et al, , 2009, induction of proinflammatory cytokines (Tohyama et al, 2009;Cho et al, 2012) or influencing cell proliferation (Ma, Jia, 2016) require an incubation of cells in the presence of 10-100 ng/mL IL17-A. Presumably, this difference can be explained by the fact that in psoriasis, T h17 cells, which are the main source of IL17-A in the body, are predominantly located in the inflamed tissue where they are needed to stabilize the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%